“I am grateful for the grace received”: religious devotions around martyrdom in cemeteries in Recife and São Paulo (1970-1980) (Tempo e Argumento, 2026)
Representations of sainthood attributed to characters and spaces in cemeteries in Brazil gained strength during the 20th century. Reports around the murder of the “Nameless girl” and the victims of the Joelma Building fire, in Recife and São Paulo, respectively, demonstrate how believers incorporate new meanings and practices into Catholic orthodoxies. Based on the analysis of periodicals and government documents, with an approach based on Cultural History, we analyze the invention of sainthoods, which happens apart of the legitimacy of the Catholic Church, and the incorporation of sociocultural practices into the orthodoxies established by the ecclesiastical hierarchy. Saint-creating processes were key for the organization of new devotions, religious action, and the invention of worship in both cities, with the movement of believers from various locations and the most diverse individual and collective needs.
Keywords: saints; Nameless girl; Joelma Building; Recife; São Paulo